Evaluation of obesity prevention effect of black ginseng on serum, liver, and hypothalamus of mice on a high-fat diet using a metabolomics approach - Ye Jin Kim; Dae Young Lee; Hye Rim Yang; Kyung-Hoan Im; Sang Un Park; Jae Geun Kim; Jae Kwang Kim (Applied Biological Chemistry, 2023)
Abstract Black ginseng is being studied to prevent obesity caused by a high-fat diet (HFD). The aim of this study was to evaluate the obesity-preventing effect of black ginseng extract (BGE) in the serum, liver, and hypothalamus of mice on an HFD using metabolomic techniques. Mice were divided into four groups which were respectively fed a normal diet (CTL), an HFD, an HFD with a low concentration of BGE (BGEL), and an HFD with a high concentration of BGE (BGEH) for 8 weeks. Metabolite profiling revealed a clear separation between the BGE diet and HFD groups. Lipid metabolism, including saturated fatty acids and cholesterol, was decreased in the BGEH mice. Specifically, neurotransmitters and intermediates of the tricarboxylic acid cycle were increased in the hypothalamus of BGEH mice. The results suggest the obesity prevention effect of black ginseng in that BGEH inhibits body fat accumulation and restores brain function damaged by HFD.